Direct accessibility of mixed-metal (iii/ii) acid sites through the rational synthesis of porous metal carboxylates1. Issue 50 (25th June 2015) - Wongsakulphasatch, S.; Nouar, F.; Rodriguez, J.; Scott, L.; Le Guillouzer, C.; Devic, T.; Horcajada, P.; Grenèche, J.-M.; Llewellyn, P. L.; Vimont, A.; Clet, G.; Daturi, M.; et al.
<x xml:space="preserve">Abstract</x> The scalable and environmentally-friendly synthesis of mixed-metal MOFs is presented.